Modern Sedimentation and Authigenic Mineral Formation in the Chew Bahir Basin, Southern Ethiopia: Implications for Interpretation of Late Quaternary Paleoclimate Records - Gebregiorgis, Daniel; Deocampo, Daniel M.; Foerster, Verena; Longstaffe, Fred J.; Delaney, Jeremy S.; Schaebitz, Frank; Junginger, Annett; Markowska, Monika; Opitz, Stephan; Trauth, Martin H.; Lamb, Henry F.; Asrat, Asfawossen (Frontiers in Earth Science, 2021)
We present new mineralogical and geochemical data from modern sediments in the Chew Bahir basin and catchment, Ethiopia. Our goal is to better understand the role of modern sedimentary processes in chemical proxy formation in the Chew Bahir paleolake, a newly investigated paleoclimatic archive, to provide environmental context for human evolution and dispersal. Modern sediment outside the currently dry playa lake floor have higher SiO2 and Al2O3 (50–70 wt.%) content compared to mudflat samples. On average, mudflat sediment samples are enriched in elements such as Mg, Ca, Ce, Nd, and Na, indicating possible enrichment during chemical weathering (e.g., clay formation). Thermodynamic modeling of evaporating water in upstream Lake Chamo is shown to produce an authigenic mineral assemblage of calcite, analcime, and Mg-enriched authigenic illitic clay minerals, consistent with the prevalence of environments of enhanced evaporative concentration in the Chew Bahir basin. A comparison with samples from the sediment cores of Chew Bahir based on whole-rock MgO/Al2O3, Ba/Sr and authigenic clay mineral δ18O values shows the following: modern sediments deposited in the saline mudflats of the Chew Bahir dried out lake bed resemble paleosediments deposited during dry periods, such as during times of the Last Glacial Maximum and Younger Dryas stadial. Sediments from modern detrital upstream sources are more similar to sediments deposited during wetter periods, such as the early Holocene African Humid Period.